2004
DOI: 10.1002/ptr.1450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypericum perforatum on marble‐burying by mice

Abstract: The effect of Hypericum perforatum extract (LI 160) at a dose that exerts an antidepressive-like effect was studied in mice in the marble-burying test. Acute Hypericum perforatum (150, 300 and 500 mg/kg, p.o.) reduced immobility time in the forced swimming test. The number of marbles buried, but not locomotor activity, was reduced by acute treatment with Hypericum perforatum (150 and 300 mg/kg, p.o.). However, this effect was not seen after chronic treatment (21 days) with Hypericum perforatum (300 mg/kg, p.o.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…In accordance with our results, the suppressive effect of St John's wort (300 mg kg À1 , p.o.) on marble-burying behaviour in mice was reported by Skalisz et al (2004). We have previously found that brain serotonin transporter occupancy by SSRIs significantly correlated well with their suppressive effects on marble-burying behaviour after oral administration in mice (unpublished observation), suggesting that St John's wort exerts its suppressive effect on marble-burying behaviour through the activation of serotonergic neurotransmission.…”
Section: Discussionsupporting
confidence: 53%
“…In accordance with our results, the suppressive effect of St John's wort (300 mg kg À1 , p.o.) on marble-burying behaviour in mice was reported by Skalisz et al (2004). We have previously found that brain serotonin transporter occupancy by SSRIs significantly correlated well with their suppressive effects on marble-burying behaviour after oral administration in mice (unpublished observation), suggesting that St John's wort exerts its suppressive effect on marble-burying behaviour through the activation of serotonergic neurotransmission.…”
Section: Discussionsupporting
confidence: 53%
“…No food or water was present. 30 min later, animals were removed, and the number of marbles at least two-third buried in the sawdust was recorded [26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…No food or water was present. The number of marbles that were at least two-thirds buried after 30 min was recorded (Skalisz et al, 2004;Dekeyne et al, 2008).…”
Section: Marble-burying Testmentioning
confidence: 99%